Poverty Reduction and Growth Trust : Review of Interest Rate Structure. (Policy Papers; Policy Paper, 2011)
This is the first review of the interest rate mechanism approved under the 2009 reforms of the Fund's concessional lending facilities. The mechanism links the Poverty Reduction and Growth Trust (PRGT) interest rate structure to world interest rates and provides a setting to differentiate interest rates across the various PRGT facilities. The framework requires reviews every two years, with the first such review to be completed by December 31, 2011.